Experimental Study on Heat Transfer Performance of Closed-loopSpray Cooling Using R134a - Zhou Nianyong; Feng Hao; Xu Hongye; Liu Wenbo; Guo Yixing; Gan Xinhai (Zhileng xuebao)
In this study, an R134a closed-loop spray cooling system was built to investigate the effects of flow rate, subcooling degree, and refrigerant charge on the steady spray cooling heat transfer performance. The experimental flow rate ranged from 0.20 to 0.25 L/min, the subcooling degree ranged from 5 to 8 ℃, and the refrigerant charge ranged from 0.95 to 1.25 kg. Results show that at a flow rate of 0.184 L/min and refrigerant charge of 0.95 kg, the maximum heat flux and surface heat transfer coefficient were 105.25 W/cm2 and 2.54 W/（cm2?℃）, respectively. At low heat flux (45.93–72.55 W/cm2), with the increase in flow rate, subcooling degree, and refrigerant charge, the surface heat transfer coefficient, overall, increased. Under higher heat flux (84.02–105.25 W/cm2), the surface heat transfer coefficient increases gradually with the increase in flow rate. The surface heat transfer coefficient initially increased and then stabilized as the refrigerant charge increased. In addition, the Jacob number Ja decreases with an increase in charge, which is unfavorable for the improvement of the surface heat transfer coefficient at higher heat flux. There is an optimal refrigerant charge to maximize the heat transfer performance of the closed spray cooling system.